Efecto de la cachaza más roca fosfatada enriquecida con microorganismos sobre la disponibilidad, absorción de P y el crecimiento del maíz en dos tipos de suelo - Castellanos González, Leónides; Prado, Renato de Mello [UNESP]; Caione, Gustavo; Moda, Leandro Rosatto; Asis, Luis C. [UNESP]; Nahas, Ely [UNESP]; Selva, Enrique Parets; de Almeida, Hilário Júnior [UNESP] (My University, 2016)
This work aims to evaluate the effect of filter cake plus phosphate rock enriched with microorganisms on availible and adsorbed P, and the growth of corn in two soils. The experiment was conducted in a greenhouse with corn plants. A totally randomized experimental design with split plot design 2 x 4 was used, with three repetitions. The first factor was constituted by the two types of soils (Haplustox and Hapludox), and the second by four fertilizer treatments to the soil, using phosphate rock of Araxá plus filter cake enriched with biofertilizers: Biopack (B), Embrafos (E) and Azotofos (A) and a control without enrichment (CO). The height of the plants, the diameter of the stall and the number of leaves per plant were evaluated at 28 and 42 days after sowing. The dry biomass and the phosphorus content in the soil and in the plants were evaluated at 42 days. The filter cake plus phosphate rock applied to the soil (with biofertilizers or not) increased the available phosphorous in Hapludox in relation to Haplustox. The treatment of Hapludox fertilized with phosphate rock plus filter cake enriched with B stood out on the rest for the P assimilated by the plants of corn. In Hapludox the values of height of the plants, diameter of the stall and dry biomass were increased in the treatments fertilized whit filter cake plus phosphate rock enriched with the three biofertilizers, while in Haplustox they were increased with the addition of B and E, without differing of the treatment without enriching.
Effect of filter cake plus phosphate rock enriched with microorganisms on available and adsorved P and the growth of corn in two soils
Keywords: Available phosphorus; Dry biomass; Filter cake; Microorganisms; Zea mays